Effects of different slow release fertilizers on nitrogen loss and cadmium migration in vegetable fields - ZHANG Jining; ZHANG Xianxian; SUN Huifeng; WANG Cong; ZHOU Sheng (浙江大学学报. 农业与生命科学版)
Based on the experimented cadmium (Cd)-contaminated vegetable fields, the effects of slow release fertilizers (coated with sulfur, phosphate and attapulgite) on soil nitrogen loss and Cd contents were studied. The results showed that, compared with the conventional fertilizer treatment, the contents of <alternatives>NO3－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/49BD2370-03B1-4caa-A414-EBCC79DD8581-M003.jpg"/></alternatives>-N and dissolved nitrogen (DN) were improved by 5.6%-22.2% and 29.6%-50.6% in the soil samples, and the contents of <alternatives>NO3－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/49BD2370-03B1-4caa-A414-EBCC79DD8581-M003.jpg"/></alternatives>-N and DN in the leaching solution were decreased by 9.4%-17.4% and 22.8%-31.8%, respectively, indicating that slow release fertilizers could relieve nitrogen loss in soil. The soil electrical conductivity, available phosphorus and available potassium contents increased by 33.5%-41.6%, 63.1%-100.0% and 27.3%-42.7%, respectively. The contents of soil total Cd and available Cd were decreased by 13.5%-16.4% and 37.6%-48.0%, respectively, compared with those of the initial soil. The above results suggest that the coated slow release fertilizers can realize the safe utilization of mildly and moderately Cd contaminated vegetable fields. It provides a theoretical basis for the scientific application of slow release fertilizers to reduce non-point source pollution and heavy metal contamination in a vegetable field.